2023
DOI: 10.1136/bmjopen-2022-066526
|View full text |Cite
|
Sign up to set email alerts
|

Association between obesity and 1-year mortality in septic patients: a retrospective cohort study

Abstract: ObjectiveSepsis is a major contributor of intensive care units (ICUs) patient mortality. Prior investigations claimed that obesity enhances overall survival (OS) of septic patients. However, the reported results were inconsistent. This study examined the association between obesity and the 1-year mortality of septic patients.DesignA retrospective cohort study.SettingThe Medical Information Mart for Intensive Care III database.Participants3145 septic patients were separated into three distinct cohorts, based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…A total of 3865 records were identified via a systematic search of databases published before March 28, 2023, and screened for inclusion based on eligibility criteria. After reviewing the titles and abstracts, 12 studies [ [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] ] were selected for inclusion in this study. Specifically, these studies reported on the association between obesity and sepsis prognosis, with 8 [ 14 , [16] , [17] , [18] , [19] , [20] , [21] , 23 ] of them focusing on overweight patients and 6 [ 14 , 16 , 18 , 20 , 21 , 35 ] of them restricting the analysis to patients with low weight.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 3865 records were identified via a systematic search of databases published before March 28, 2023, and screened for inclusion based on eligibility criteria. After reviewing the titles and abstracts, 12 studies [ [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] ] were selected for inclusion in this study. Specifically, these studies reported on the association between obesity and sepsis prognosis, with 8 [ 14 , [16] , [17] , [18] , [19] , [20] , [21] , 23 ] of them focusing on overweight patients and 6 [ 14 , 16 , 18 , 20 , 21 , 35 ] of them restricting the analysis to patients with low weight.…”
Section: Resultsmentioning
confidence: 99%
“…This meta-analysis comprised 12 studies [ [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] ] encompassing data from multiple countries or regions with a total of 521,207 individuals, and two of which were prospective cohort studies. The follow-up time varied across the studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations